ANALISIS BUKU TEKS BIOLOGI KELAS XII SMA BERDASARKAN LITERASI SAINS PADA MATERI BIOTEKNOLOGI - Sugiharti, Sindi; Sugandi, Muhamad Kurnia; Aripin, Ipin (Mirabilis : Journal of Biology Education, 2023)
The results of the 2018 Program For International Student Assessment (PISA) survey show that the scientific literacy ability of Indonesian students is still low. One of the factors that are directly related to learning activities that affect the level of scientific literacy ability is the use of textbooks. The purpose of this study was to determine the aspect of scientific literacy that appears in the Biology textbook for class XII SMA on biotechnology material. This research is a qualitative research with descriptive method. The results of data analysis showed that the category of science knowledge was the category that most appeared, namely 46.4% (book X), 39.75% (book Y), and 60.5% (book Z), the category of investigation of the nature of science was 2, 76% (book X), 6.83% (book Y), and 5.09% (book Z), science as a way of thinking is 12.15% (book X), 14.9 (book Y), and 10 ,82% (book Z), then the interaction of science, technology, and society by 38.67% (book X), 38.5% (book Y), and 23.56% (book Z). This data illustrates that the 12th grade biology textbooks used in high school have not shown balanced proportions.